Integrated management of weeds in carrot culture - Vieira, R. D.; Vieira, W. D.; Ferreira, P. R. N.; Silva, P. M. (Scientific Electronic Archives, 2018)
The culture of carrot is characterized by being one of the most important vegetables when it comes to cultivation, trade, consumption and human health benefits. Objective with this revision work out and discuss the general characteristics of culture, and, in addition, point control methods of weeds that affect the main producing regions. It appears throughout the text that the carrot is a very important plant, with agronomic techniques that enable higher performance roots. The existence of health, nutrition and hydration in the culture medium are also indispensable. In sanity when it focuses on weeds, can quote the Biological control methods, Chemical, Physical, Cultural etc. The combination of the different methods, with preventive and frequent actions can generate a higher yield of all the possibilities, instead of taking isolated methods. Currently, less use of herbicides and the like has been valued by consumers, something that can increase the overall viability of the farming activity, strengthening phytosanitary control techniques.